2004
DOI: 10.1051/0004-6361:20041241
|View full text |Cite
|
Sign up to set email alerts
|

An unbiased search for the signatures of protostars in the ρ  Ophiuchi A molecular cloud

Abstract: Abstract. We present an unbiased search for molecular hydrogen emission in the L1688 cloud within the ρ Ophiuchi molecular cloud complex. Our near-infrared survey covers a connected region of extent 35 × 35 . We detect several new H 2 flows but the total number of detected outflows is low and is consistent with the paucity of Class 0 and Class 1 sources in the molecular cloud. From the spatial distribution, their collimation and the individual shapes of the bow shocks, we suggest possible candidates for the ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
97
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 24 publications
(100 citation statements)
references
References 47 publications
(73 reference statements)
3
97
0
Order By: Relevance
“…Archival SofI images (PID: 65.I-0576(A) and 67.C-0284(A)) obtained in July 2000 and August 2001, and published by Gómez et al (2003); Khanzadyan et al (2004) served as the first epoch data. The newly-acquired SofI images provided the second epoch to measure the proper motions of the H 2 emission-line features in MHOs.…”
Section: Proper Motion Measurementsmentioning
confidence: 99%
See 2 more Smart Citations
“…Archival SofI images (PID: 65.I-0576(A) and 67.C-0284(A)) obtained in July 2000 and August 2001, and published by Gómez et al (2003); Khanzadyan et al (2004) served as the first epoch data. The newly-acquired SofI images provided the second epoch to measure the proper motions of the H 2 emission-line features in MHOs.…”
Section: Proper Motion Measurementsmentioning
confidence: 99%
“…Davis et al (2010) strictly defined molecular hydrogen emissionline objects (MHOs) as the near-infrared manifestations of outflows, and presented a comprehensive catalog of around 1000 MHOs. Deep, wide-field near-infrared imaging with the combination of narrow-band H 2 filter and the corresponding A&A 553, A41 (2013) filter for continuum emission such as a Ks filter has become a very efficient method to detect and identify MHOs (Stanke et al 2002;Khanzadyan et al 2004;Davis et al 2008;Froebrich et al 2011). Morphology, proper motion, as well as association with an HH object or CO outflow, can all provide information concerning the location of the driving source.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This would lead to a precession period of about four years in order to generate the structures (A, B, and C) at each side of the so-called cavity (opening angle ∼65 • ). This period is too short when compared with typical jet fast precession periods (Rosen & Smith 2004;Caratti o Garatti et al 2008), and not consistent with the longer period suggested by the large-scale jet images (see f08-01 field in Khanzadyan et al 2004).…”
Section: Discussionmentioning
confidence: 56%
“…IRS 54 is known to possess a large-scale S-shaped bipolar jet as traced by a chain of H 2 knots 1 extending over several arcminutes (feature f08-01 in Khanzadyan et al 2004). From wide-field H 2 images, the jet appears to precess with a position angle (PA) changing from ∼72 • in the outermost knots passing through ∼78 • in the middle part of the jet down to 90 • closest to the source (MHO 2129; see also Fig.…”
Section: Discussionmentioning
confidence: 99%